A Program Evaluation of M.Ed. English Language Education of Tribhuvan University - Priya, Pushpa (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
The purpose of this research was to review English language education program of Tribhuvan University using Stufflebeam’s CIPP model. The paper investigated university teachers’ and students’ perception on current curriculum of MEd in English language education based on CIPP model. Qualitative research approach was adopted to collect the data. Four research participants were purposely selected from Central Department of Education, Tribhuvan University. The study reports that University teachers’ are positive towards context and product process; but unsatisfied with process and input process. And the students’ are positive towards input and product process; but unsatisfied with process and context process. This requires an immediate attention on the part of curriculum designer and policy maker to internalize the strengths and weakness of the curriculum and redesign accordingly.